In vitro evaluation of tigecycline synergy testing with nine antimicrobial agents against Enterobacter cloacae clinical strains - Korczak, Lukasz; Majewski, Piotr; Rombel, Krzysztof; Iwaniuk, Dominika; Sacha, Pawel; Modzelewski, Mateusz; Tryniszewska, Elzbieta (Frontiers in Microbiology, 2024)
Enterobacterales (especially carbapenem-resistant) are considered an urgent threat to public health. The available antibiotic therapy is limited due to the increase of multidrugresistant (MDR) strains. Tigecycline, a minocycline derivative, has emerged as a potential key agent in the treatment of MDR isolates. The aim of the study was to evaluate the synergistic effect of tigecycline in combination with nine antimicrobial agentsceftazidime/avibactam, colistin, ertapenem, gentamicin, imipenem, levofloxacin, meropenem/vaborbactam, polymyxin B, and rifampicin. Eighty clinical Enterobacter cloacae strains were obtained from patients of two University Hospitals in Bialystok, Poland. The E-test method was used to determine synergistic interactions. Among all combinations, synergy was reported in 61% of cases, addition in 32%, and indifference in 7%. The highest synergy rates were observed in tigecycline combinations with: ceftazidime/avibactam (60/80; 75%), imipenem (60/80; 75%), polymyxin B (55/80; 68,75%) and rifampicin (55/80; 68,75%), while the lowest synergy rate was noted in tigecycline-levofloxacin (26/80; 32,5%). The tigecycline-gentamicin showed the highest rate of indifference; antagonism, was not observed in any combination. In conclusion, tigecycline appears more suitable for use in combination therapy rather than as monotherapy and can be effectively paired with various antimicrobial agents against MDR E. cloacae. Further research will be necessary to confirm these results.